A Study of Critical Thinking Development Through Literary Analysis in Language Education - Rangga Winata; Sukoco Dwipantari; Anggi Prajadiningrat (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study investigated the development of critical thinking skills through literary analysis in a literary appreciation class. Employing a mixed-methods approach, the research utilized two main instruments: a critical thinking skills assessment test and structured literary analysis assignments. The critical thinking assessment test, adapted from the Watson-Glaser Critical Thinking Appraisal, measured students’ abilities in inference, recognition of assumptions, deduction, interpretation, and evaluation of arguments. A paired sample t-test comparison of pre-test and post-test scores indicated significant improvements in all dimensions of critical thinking. Specifically, the mean pre-test score of 65.3 increased to 78.6 post-test, reflecting substantial gains in critical thinking skills (t(39) = 9.45, p < 0.001). Qualitative data from student reflections and interviews further supported these findings, revealing key themes in the development of critical thinking skills. Students reported enhanced understanding of texts, improved analytical skills, and better interpretation abilities. Additionally, exposure to diverse socio-cultural contexts through literature allowed students to appreciate different perspectives. This was corroborated by students' feedback, which highlighted their growth in critical thinking through the structured analysis and discussion of literary texts. The study underscores the effectiveness of integrating literary analysis into language education to develop critical thinking skills. The combination of quantitative improvements and qualitative insights provides strong evidence of the positive impact of literary analysis on students' cognitive abilities and their ability to engage with complex ideas.